2004
DOI: 10.1016/s0002-9440(10)63140-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Survivin Expression in Mantle Cell Lymphoma Is Associated with Cell Proliferation and Survival

Abstract: Survivin is a member of the inhibitor of apoptosis protein family that is expressed inMantle cell lymphoma (MCL) is a malignant lymphoproliferative disorder characterized by the proliferation of CD5ϩ, CD23-monoclonal B cells containing the chromosomal translocation t(11;14)(q13;q32) which places the cyclin D1 gene under the transcriptional control of the immunoglobulin heavy chain enhancer elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 48 publications
8
67
1
2
Order By: Relevance
“…Survivin is a cytoplasmic protein, and the nuclear localization is required for its function in the proliferation and apoptosis regulation [32][33][34]. In the present study, we showed that LMP1 could promote Survivin to accumulate in the nuclei and bind with CDK4.…”
Section: Initiation Of Survivin/ Cdk4 Complex Formation In the Nucleisupporting
confidence: 49%
“…Survivin is a cytoplasmic protein, and the nuclear localization is required for its function in the proliferation and apoptosis regulation [32][33][34]. In the present study, we showed that LMP1 could promote Survivin to accumulate in the nuclei and bind with CDK4.…”
Section: Initiation Of Survivin/ Cdk4 Complex Formation In the Nucleisupporting
confidence: 49%
“…Finally, in two recent papers, nuclear Survivin overexpression has been associated with poor prognosis in mantle cell lymphoma (Martinez et al, 2004) and oesophageal squamous cell carcinoma (Grabowski et al, 2003). The results of these studies contributed to the confusion regarding the role of nuclear expression of Survivin.…”
Section: Discussionmentioning
confidence: 99%
“…Different prognostic significance of BIRC5 nuclear labeling in several tumor types has been reported in recent years, [45][46][47][48][49][50] as summarized in reference Li et al 51 For example, correlation of BIRC5 nuclear (but not cytoplasmic) staining with poor prognosis has been reported in ependymoma, esophageal squamous cell carcinoma, hepatocellular carcinoma, mantel cell lymphoma, and non-small cell lung cancer. [45][46][47][48] Paradoxically, BIRC5 nuclear staining was reported to be associated with better prognosis in gastric cancer and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48] Paradoxically, BIRC5 nuclear staining was reported to be associated with better prognosis in gastric cancer and breast cancer. 49,50 It has been proposed that variations in immunostaining and interpretation might be among the contributing factors to these conflicting results.…”
Section: Discussionmentioning
confidence: 99%